FOUNDATION RIGHTS OF UNDERGROUND BUILDING FROM HORIZONTAL SEPARATION PRINCIPLE’S PERSPECTIVE - Missariyani, Missariyani (Tadulako Law Review, 2019)
This paper discusses the foundation rights of underground buildings from the perspective of horizontal separation principle. The first discussion is about the foundation rights of underground buildings according to the principle of horizontal separation and legal construction in the utilization of the right to use underground space for buildings. Furthermore, it will be discussed more specifically the legal basis of state authority in land use, licensing in the construction of buildings under the basement, building rights as the object of building law, construction of underground use rights law as a new concept in national agrarian law.